2001
DOI: 10.1021/bi011088b
|View full text |Cite
|
Sign up to set email alerts
|

A GCN4 Variant with a C-Terminal Basic Region Binds to DNA with Wild-Type Affinity

Abstract: Basic-region leucine zipper (bZip) proteins contain a bipartite DNA-binding motif consisting of a leucine zipper dimerization domain and a basic region that directly contacts DNA. In all naturally occurring bZip proteins, the basic region is positioned N-terminal to the leucine zipper. We have designed a series of model bZip peptides in which the basic region of the yeast transcriptional activator GCN4 is placed C-terminal to its leucine zipper. DNA-binding studies demonstrate that the optimal reverse GCN4 (rG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…(GCN4) 1-8 -(FOS) 9-28 , (CYS3) 1-8 -(FOS) 9-28 , (FOS) 1-8 -(GCN4) 9-28 , and (FOS) 1-8 -(CYS3) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The data in Figs.…”
Section: Intrinsic Helicities Inferred From Simulation Results Are Inmentioning
confidence: 99%
See 1 more Smart Citation
“…(GCN4) 1-8 -(FOS) 9-28 , (CYS3) 1-8 -(FOS) 9-28 , (FOS) 1-8 -(GCN4) 9-28 , and (FOS) 1-8 -(CYS3) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The data in Figs.…”
Section: Intrinsic Helicities Inferred From Simulation Results Are Inmentioning
confidence: 99%
“…S1 of Supplementary Material). Experiments have shown that bZIP-bRs are necessary and sufficient for DNA binding, [11][12][13][14][15] while the leucine zipper regions are required for dimerization. Furthermore, stopped-flow fluorescence experiments show that bZIP-bRs bind their cognate half-sites independently as monomers, 11,16,17 and available spectroscopic evidence suggests that, in complex with DNA, basic regions form α-helical conformations irrespective of the presence or the absence of the leucine zipper region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the straightforward substitutions of the dimerization domain described before, the GCN4 bZIP-binding domain has inspired the development of a variety of synthetic, sequenceselective DNA-binding peptides [28][29][30][31][32][33][34] . Interestingly, although in all naturally occurring bZIP proteins the basic region is positioned N-terminal to the leucine zipper, Oakley and coworkers 35 showed that model 'reverse' bZIP peptides, in which the basic region of the bZIP factor GCN4 is placed C-terminal to its leucine zipper, can specifically bind to inverted DNA sites. Thus, while natural GCN4 C/C-terminal dimers specifically bind to ATF/CREB (5 0 -ATGA(c/g)TCAT-3 0 ) or AP1 (5 0 -ATGA(c)TCAT-3 0 ) sites, reversed N/N-terminal dimers bind to inverted 5 0 -TCAT(y)ATGA-3 0 sites.…”
mentioning
confidence: 99%
“…The GCN4 bZip is a common template for protein design (19,39,40). Our DNA looping peptides were inspired by the work from the Oakley laboratory in which the basic DNA-binding region was fused to the C-terminus of the leucine zipper instead, to make the reverseGCN4 peptide (29). They demonstrated that reverseGCN4 has high affinity and specificity for a DNA target in which the palindromic CREB binding site recognized by GCN4 (5′- ATGAC| GTCAT-3′) is inverted to give the Inv-2 site (5′- GTCAT |ATGAC-3′); the underlining indicates the specific half-site recognized by each basic region.…”
Section: Resultsmentioning
confidence: 99%
“…This palette has been used to engineer peptides with new ligand-binding properties (27,28). The GCN4 basic region leucine zipper (bZip) DNA-binding domain has been a common template, and Oakley and coworkers (29) have shown that transposing its N-terminal basic DNA-binding helix to the C-terminus provides a new sequence-specific DNA-binding protein. Here, we have extended the diversity of coiled-coil applications to include DNA looping, by appending both N- and C-terminal DNA-binding domains to a central coiled-coil dimerization domain, creating leucine zipper dual-binding (LZD) peptides.…”
Section: Introductionmentioning
confidence: 99%